Assessing resistance towards the adoption of cashless payment: a survey among Generation X in Klang Valley / Mary Wang Xie Ling ... [et al.] - Wang, Mary Xie Ling; Chua, Chua; Ho, Hong Ren; Mohd Johan, Mohd Remie; Annuar, Nursyamilah (Universiti Teknologi MARA, Perlis, 2023)
Adopting cashless payments at every level, including consumers, businesses, and the government, plays a vital role in Malaysia's transition to an entirely cashless economy. To boost Malaysian consumers' adoption of cashless payments, the barriers that hinder their adoption must first be identified. This study incorporates the obstacles to resistance proposed by the Innovation Resistance Theory (IRT) model with an additional external variable targeted at Gen X due to limited resistance studies on this age cohort in Malaysia. The barriers studied were usage, value, risk, tradition, and merchant acceptance barriers. Thus, this study aims to assess the obstacles that hinder the adoption of cashless payments and identify the relationship between the barriers and resistance towards adopting cashless payments among Gen X in the Klang Valley. The methodology used in this study is a survey approach to distributing questionnaires. Various analyses were performed on the 384 responses from Gen X in the Klang Valley region. The study found that usage, tradition, and image barriers significantly and positively affect resistance towards adopting cashless payment among Gen-Xers in the Klang Valley. However, value, risk, and merchant acceptance barriers did not considerably affect resistance towards adopting cashless payment among Gen-Xers in the Klang Valley. Therefore, it is suggested that future studies delve deeper into the research framework model proposed, which uses the IRT model and the additional external variables presented to gain more valuable insights into consumer resistance.